PERANCANGAN UNIVERSAL PROCESS CONTROL (STUDI KASUS:PUSAT PELATIHAN KERJA DAN PENGEMBANGAN INDUSTRI PASAR REBO) - Irawati Irawati; Ismuharram Ismuharram (Institut Teknologi dan Bisnis Swadharma, 2021)
Training institutions need a lot of teaching aids because graduates need to be prepared and adapted to the world of work, both their skills and equipment. For Industrial Electronics training activities, the equipment needed is one of which is an integrated display between mechanics and electronics so that it can be directly applied, Universal Process Control is equipment that has been prepared by the supplier of goods at the Rebo Market Industrial Development Job Training Center training institution. The automation of a production system based on a PLC (Programmable Logic Controller) can be demonstrated with the JP-UCT 500, this trainer provides the completeness of the Logic Panel and Logic Panel used is PLC + HMI + IO integration Autonic LP-S070-T9D6-C5T, work system and programming LP-S070-T9D6-C5T as the main controller in the process while the use of proximity sensors, thermocouples, solenoid valves and water pumps, heating in control systems, proximity sensors have sensitivity distance to read objects in clear water 8.71 + 0.17 mm, black coffee water 8.67 + 0.08 mm and floor cleaning fluid 8.61 + 0.08 mm